2002
DOI: 10.1177/154405910208100309
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing Cardiovascular Disease and Periodontitis: A Follow-up Study

Abstract: Periodontal infections in individuals with pre-existing heart disease are believed to increase the risk for future coronary heart disease (CHD) events. The goal of this study was to search for an association between periodontitis and CHD events among individuals with pre-existing heart disease, reported in the First National Health and Nutrition Examination Survey Epidemiologic Follow-up Study. Dentate adults (n = 636) with a history of pre-existing cardiovascular disease were followed for CHD events. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
1
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 18 publications
(9 reference statements)
2
29
1
1
Order By: Relevance
“…In addition to these risk factors, diabetic Pima Indians with severe periodontal disease had lower BMI, which may reflect underlying illness because it is associated with higher mortality rates in this population (18). Heavy smoking is strongly associated with both periodontal disease and CVD (22) and undoubtedly confounds the relationship between these diseases (23)(24)(25)(26)(27)(28). In the present study, however, smoking was not associated with periodontal disease.…”
Section: Discussioncontrasting
confidence: 47%
“…In addition to these risk factors, diabetic Pima Indians with severe periodontal disease had lower BMI, which may reflect underlying illness because it is associated with higher mortality rates in this population (18). Heavy smoking is strongly associated with both periodontal disease and CVD (22) and undoubtedly confounds the relationship between these diseases (23)(24)(25)(26)(27)(28). In the present study, however, smoking was not associated with periodontal disease.…”
Section: Discussioncontrasting
confidence: 47%
“…This is consistent with other studies. [27][28][29]31 Studies reporting on this association have used a variety of definitions of periodontal disease as an exposure, and our own work has used Ͼ1 definition. Because there is almost no information on which clinical periodontal measures and their severity may be related to systemic conditions, the range of exposures reported in the literature may be one reason for the inconsistency in findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have found either nonsignificant positive trends or no association after adjustment for variables considered to be confounders. [27][28][29][30][31] Concerns about the validity of the periodontitis-cardiovascular disease associations have been expressed. A review by Danesh 32 noted that studies were based on clinical measures of periodontal disease and did not have direct measures of the infection, such as bacterial counts or systemic antibody levels to oral pathogens.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] Infections of periodontal structure could accelerate atherosclerosis by promoting a systemic inflammatory status through release of endotoxins, heatshock proteins, or acute-phase reactants. 26,27 Periodontitis and cardiovascular disease might also share some explanatory risk factors such as diabetes mellitus, smoking, and dyslipidemia.…”
Section: Periodontitis and Cardiovascular Diseasementioning
confidence: 99%
“…3 Established risk factors for periodontal disease are dental plaque, calculus, age, genetics, smoking, and diabetes. 4 At least 9 cohort studies [5][6][7][8][9][10][11][12][13] examined the association between periodontal disease and coronary heart disease (CHD), with conflicting results. An overview of these studies 14 showed a 15% excess risk of CHD in association with periodontal disease, with 95% confidence intervals ranging from 8% to 122%.…”
mentioning
confidence: 99%